KARAKTERISTIK FISIK DAGING SAPI HAS DALAM PADA PERENDAMAN BERBAGAI BAGIAN BUAH NANAS - Inti Mulyo Arti; Adinda Nurul Huda; Evan Yonda Pratama (FoodTech: Jurnal Teknologi Pangan, 2019)
The purpose of this study was to determine changes in physical characteristics in tenderloin beef due to soaking in various parts of pineapple with different soaking times. The portion of pineapple that is used includes the meat, middle weevil, bark and leaves. The treatment of beef has inside without soaking pineapple was stated as control. The measured variables are pH, weight and temperature of beef has in. Observations were carried out for 0, 10, 20, 30, 40, 50 to 60 minutes soaking. The results showed that beef has been deep for 60 minutes soaking with the juice of the pineapple fruit changes in pH, weight and temperature. The pH value of meat on soaking meat, tubers and pineapple leaves is relatively the same. The weight of pineapple flesh increases along with the immersion of the pineapple juice. The temperature of beef has decreased in except for soaking with tuber juice and pineapple meat.